Silencing of connexin 43 suppresses invasion, migration and lung metastasis of rat hepatocellular carcinoma cells - Ogawa K. (2014)
To reduce cancer mortality, understanding of mechanisms of cancer metastasis is crucial. We have established six rat hepatocellular carcinoma (HCC) cell lines, which exhibit differing metastatic potential to the lung after inoculation into the tail veins of nude mice. In the present experiment, we investigated the process of cell attachment to metastatic sites and possible regulating factors. One hour after inoculation, two of two HCC cell lines with high metastatic potential and one of two HCC cell lines with low metastatic potential exhibited many attached cells in the lung. One day after inoculation, lung metastatic foci were observed only with highly-metastatic cells with elevated connexin 43 (Cx43) expression as assessed by cDNA array analysis. Furthermore, 24 or 48 h after transfection of an siRNA targeting Cx43, in vitro invasion and migration were suppressed by 68% (P < 0.001) and 36% (P < 0.05) compared with control-siRNA transfected cells, despite no differences in cellular morphology, cell proliferation or apoptotic activity. Moreover, the number of metastatic nodules per lung area in nude mice was significantly (P < 0.01) reduced. In conclusion, suppression of Cx43 expression in tumor cells reduced in vitro migration and invasion capacity and in vivo metastatic ability so that Cx43 has potential as a molecular target for prevention of cancer metastasis with Cx43 overexpressing tumors. © 2012 Japanese Cancer Association.